All Days 2003
DOI: 10.2118/81484-ms
|View full text |Cite
|
Sign up to set email alerts
|

Wettability and Relative Permeability of Lower Cretaceous Carbonate Rock Reservoir, Saudi Arabia

Abstract: Results and discussions in this paper relate to a Lower Cretaceous carbonate reservoir located in southeastern Saudi Arabia. It is a heterogeneous carbonate formation with various facies due to diagenetic alteration of the original rock fabric. The reservoir is large and prolific with mixed-wet characteristics. Because of the economic importance and variety of oil-recovery mechanisms operative or possible in the reservoir, the multiphase recovery behavior has been extensively studied. Also, various wettability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Rock Quality Influence on Wettability. Several researchers have observed that the extent of wettability alteration towards oil-wet in Middle East carbonates is inversely correlated to the amount of microporosity in the rock (Marzouk et al 1995;Okasha et al 2003). To investigate this hypothesis, we have plotted the invaded zone n exponent against the fraction of total pore volume that is in the micropores.…”
Section: Analysis Of Dielectric Log Datamentioning
confidence: 99%
“…Rock Quality Influence on Wettability. Several researchers have observed that the extent of wettability alteration towards oil-wet in Middle East carbonates is inversely correlated to the amount of microporosity in the rock (Marzouk et al 1995;Okasha et al 2003). To investigate this hypothesis, we have plotted the invaded zone n exponent against the fraction of total pore volume that is in the micropores.…”
Section: Analysis Of Dielectric Log Datamentioning
confidence: 99%
“…After the composite core was aged with dead and live oil, it was expected to be weak oil–wet or mixed wet behavior for such carbonate rocks. 51 , 52 …”
Section: Experimental Workmentioning
confidence: 99%
“…A relative permeability and wettability study was reported for a Lower Cretaceous carbonate by Okasha [4]. Samples of 1.5 in.…”
Section: B General Carbonate Core Samples Studiesmentioning
confidence: 99%